2008
DOI: 10.1373/clinchem.2007.090837
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pro-MMP-7 as a Serum Marker for Renal Cell Carcinoma by Use of Proteomic Analysis

Abstract: Background: No validated renal cell carcinoma (RCC) marker is known for detection of asymptomatic disease in selected populations or for prognostic purposes or treatment monitoring. We identified immunogenic proteins as tumor markers for RCC by combining conventional proteome analysis with serological screening, and we investigated the diagnostic clinical value of such markers in serum. Methods: We studied the immunogenic protein expression profile of CAL 54, a human RCC cell line, by 2-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 41 publications
0
32
0
1
Order By: Relevance
“…Our findings suggest that these two MMP-7 genotypes may not play a critical role in mediating susceptibility to RCC. The rational for focusing on the MMP-7 promoter polymorphisms, A-181G and C-153T, is based on the phenotypic findings which report that MMP-7 may serve as a promising serum marker for the prediction of RCC (19)(20)(21). In 2008, Sarkissian and his colleagues examined the serum levels of MMP-7 among healthy subjects, control patients and 30 RCC patients and found that MMP-7 was significantly higher in RCC patients than the other two groups (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings suggest that these two MMP-7 genotypes may not play a critical role in mediating susceptibility to RCC. The rational for focusing on the MMP-7 promoter polymorphisms, A-181G and C-153T, is based on the phenotypic findings which report that MMP-7 may serve as a promising serum marker for the prediction of RCC (19)(20)(21). In 2008, Sarkissian and his colleagues examined the serum levels of MMP-7 among healthy subjects, control patients and 30 RCC patients and found that MMP-7 was significantly higher in RCC patients than the other two groups (19).…”
Section: Discussionmentioning
confidence: 99%
“…The rational for focusing on the MMP-7 promoter polymorphisms, A-181G and C-153T, is based on the phenotypic findings which report that MMP-7 may serve as a promising serum marker for the prediction of RCC (19)(20)(21). In 2008, Sarkissian and his colleagues examined the serum levels of MMP-7 among healthy subjects, control patients and 30 RCC patients and found that MMP-7 was significantly higher in RCC patients than the other two groups (19). In the same year, Ramankulov and his colleagues reported that similar MMP-7 levels were found in controls and patients with non-metastatic RCCs , while MMP-7 serum levels were significantly elevated in metastatic RCCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the article by Sarkissian et al (1 ) reporting the identification of serum matrix metalloproteinase-7 (MMP-7) 1 as a marker for renal cell carcinoma (RCC). For the purpose of identification, the authors used sera from healthy individuals and RCC patients and combined 2-dimensional electrophoresis of an RCC cell-line supernatant and an immunoblotting procedure.…”
Section: To the Editormentioning
confidence: 99%
“…In contrast, the 95th percentile they observed in their control group (3.29 g/L vs our 3.35 g/L) suggested that these concentration differences did not exist in the healthy participants of the 2 studies. Because the same recombinant human MMP-7 was used as a calibrator in both assays, it can be assumed that MMP-7 forms possibly typical for RCC patients are more sensitively detected by the assay of Sarkissian et al (1 ) than by the R&D MMP-7 assay we used. Different assay designs including the use of the mentioned specific antibodies could affect the assay sensitivity, but autoantibodies to pro-MMP-7 occurring in sera of RCC patients (1 ) could also interfere with measurement of MMP-7.…”
Section: To the Editormentioning
confidence: 99%